TRAFFIC MODELING IN UAV/RPAS COMMUNICATION CHANNEL - Grekhov, Andrii; Ilnytska, Svitlana; Kondratiuk, Vasyl (Proceedings of National Aviation University (archive), 2020)
This study is devoted to obtaining the traffic characteristics of communication channel between the Remotely Piloted Air System (RPAS) and the Base Station, the model of which was created in professional software NetCracker. The dependencies of dropped packets, message Travel Time (TT) and HUB Average Utilization on the Transaction Size (TS), the link bandwidth and the Bit Error Rate (BER) for different distribution laws of Time Between Transactions (TBT) were analyzed. It was observed that for smaller TBT the lower transaction size can be transmitted, which is true for all distributions. But the lowest percentage of packet loss is observed for the LogNormal distribution. Additionally, it was observed that the TT does not depend on the value of the TBT parameter with the Exponential or LogNormal distribution laws, which is not true for the Const law. Hub utilization does not exceed ≈ 20% for all distributions with 1 s TBT. Nevertheless, the maximal TS for LogNormal law is ten times bigger than for other laws. The transaction TT decreases with the transmission rate increase, and for T3 bandwidth it equals to 0.5 s approximately for all considered distributions. However, the smallest percentage of packet loss and HUB utilization is observed for the LogNormal law. The TT does not exceed 1 s for low BER values for all TBT distributions. Such numerical analysis allows us set up and change traffic parameters while observing the results under specified transmission modes.